Preliminary phylogenetic and biogeographic considerations of the genus Sorghastrum (Poaceae: Andropogoneae) - Dávila Aranda, Patricia (Instituto de Ecología, A.C., 1991)
By means of a phylogenetic analysis using cladograms, a preliminary hypothesis pointing out relationships between the genus Sorghastrum and related genera, as well as among the species of the genus is suggested. In addition, based on the phylogenetic analysis, as well as present and past distribution patterns, a working hypothesis explaining a possible place of origin of the genus is proposed.